Structural mechanism of cooperative regulation of calcium-sensing receptor-mediated cellular signaling. Issue 17 (October 2020) - Deng, Xiaonan; Xin, Yao; Miller, Cassandra Lynn; Hamelberg, Donald; Kirberger, Michael; Moremen, Kelley W; Hu, Jian; Yang, Jenny J
Abstract : Calcium-sensing receptors (CaSRs) play a central role in regulating extracellular calcium (Ca 2+ ) homeostasis and many (patho)physiological processes. This regulation is primarily orchestrated in response to extracellular stimuli via the extracellular domain (ECD). This paper first reviews the modeled structure of the CaSR ECD and the prediction and investigation of the Ca 2+ and amino acid-binding sites. Several recently solved X-ray structures are then compared to support a proposed CaSR activation model involving functional cooperativity. The review also discusses recent implications for drug development. These studies provide new insights into the molecular basis of diseases and the design of therapeutic agents that target CaSR and other family C G protein-coupled receptors (cGPCRs).